On the nature of asymmetry of nucleation centers activity in ultrathin Co films and Co/Pt multilayers - Iunin, Yu.L.; Kabanov, Yu.P.; Nikitenko, V.I.; X.M. Cheng; Shapiro, A.J.; C.L. Chien; Shull, R.D. (Functional Materials, 2008)
Magnetization reversal in ultrathin Pt(10 nm)/Co(0.6 nm)/Pt(3 nm) magnetic films and Pt(10 nm)/[Co(d)/Pt(1 nm)]n/ Pt(2 nm) (d = 0.4, 0.6, 0.8 nm, n = 2, 4) multilayers with perpendicular anisotropy has been studied using Kerr microscopy. These materials demonstrate unusual effects of activity asymmetry of nucleation centers and domain wall motion. The field dependences of these effects have been studied and the asymmetry of the domain wall nucleation has been found to be suppressed by application of a magnetic field much stronger than the sample coercivity. The asymmetry comes back after several reversals at a lower field magnitude. The asymmetry of domain wall velocity decreases abruptly and vanishes as the reversal field increases in low coercivity ultrathin Co films. The effect recovers as in the reversal field value decreases. A role of the Co/Pt interface defects and nonlinear spin excitations in these phenomena is discussed.